Bauran Pemasaran Produk Amplang pada Usaha Mikro Kecil dan Menengah (UMKM) Deluga - Aditya, Muhammad Zulthan; Juliani, Juliani; Darmasetiadi, Doni (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Deluga Micro, Small and Medium Enterprises (MSMEs) produce amplang made from flat fish which turns river catches into value-added products. To compete with similar products, manufacturers need to pay attention to appropriate marketing strategies. The aim of this research is to determine consumer satisfaction with the marketing mix (Marketing Mix) Deluga MSME, research was conducted for 5 months, starting from November 2024 to April 2025. The sampling method used Accidental Sampling carried out randomly and willing to be interviewed with a total of 25 respondents. This research uses descriptive analysis methods. The results show that consumer satisfaction with the marketing mix (Marketing Mix) of Deluga amplang products shows that there are five elements included in the satisfaction category, namely product (8.76), price (8.6), promotion (7.96), and process (8.76). Apart from that, two elements that are included in the very satisfied category are people (9.08) and physical form (8.96). However, there is one element that is included in the dissatisfied category, namely place (5.08), because the sales location is considered less strategic. Based on cumulative calculations, an average score of 57.2 is obtained, which is included in the satisfied category. This shows that in general, consumers are satisfied with the marketing mix carried out by MSME Deluga.